2021
DOI: 10.1097/corr.0000000000001915
|View full text |Cite
|
Sign up to set email alerts
|

Poor Bone Quality, Multilevel Surgery, and Narrow and Tall Cages Are Associated with Intraoperative Endplate Injuries and Late-onset Cage Subsidence in Lateral Lumbar Interbody Fusion: A Systematic Review

Abstract: Background A major complication of lateral lumbar interbody fusion (LLIF) is cage subsidence, which may lead to clinical problems, including loss of disc height correction, altered spinal alignment, recurrent pain, and vertebral body fracture. A thorough review of the current knowledge about the risk factors for the two types of cage subsidence after LLIF-intraoperative endplate injury and late-onset cage subsidence-could bring attention to well-established risk factors for clinical consideration while identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 49 publications
(208 reference statements)
1
24
1
Order By: Relevance
“…Cage subsidence was the main factor affecting the SLA and DH loss reported in previous study [17,26] and in the present study, the loss of SLA was significantly larger in the subsidence segment. Previous research has reported multiple risk factors associated with cage subsidence such as BMD, inappropriate cage height and cage position [21,[27][28][29][30][31]. The results of this study were similar to those of previous studies showing that L1 CT HU < 110, cage height > preoperative MDH, and CPR < 50% were significantly associated with cage subsidence.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Cage subsidence was the main factor affecting the SLA and DH loss reported in previous study [17,26] and in the present study, the loss of SLA was significantly larger in the subsidence segment. Previous research has reported multiple risk factors associated with cage subsidence such as BMD, inappropriate cage height and cage position [21,[27][28][29][30][31]. The results of this study were similar to those of previous studies showing that L1 CT HU < 110, cage height > preoperative MDH, and CPR < 50% were significantly associated with cage subsidence.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study were similar to those of previous studies showing that L1 CT HU < 110, cage height > preoperative MDH, and CPR < 50% were significantly associated with cage subsidence. Patients with T<-2.5 showed a higher risk of developing cage subsidence [27], however, the T-score provided by dual-energy X-ray absorptiometry may underestimate osteoporosis in patients with lumbar degenerative disease. L1 CT HU ≤ 110 for defining osteoporosis with high specificity and sensitivity [18] and Wu et al reported that patients with lower CT HU were prone to intraoperative endplate injury and delayed cage subsidence but this did not affect the clinical outcomes [27].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Older age, female sex, cage size, multilevel cases, and osteoporosis may be risk factors for cage subsidence [ 24 , 25 , 26 , 27 ]. A systematic review reported that patients with poorer bone quality, those older than 65 years, and women should be counseled about high risks of both types of cage subsidence [ 28 ]. Anecdotally, it is also said that the cage subsidence may differ depending on the supplementary instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to bony stenosis, we believe that endplate collapse is one factor leading to intervertebral foramen restenosis. Since LLIF completely increases the intervertebral height by inserting large cage, once the graft subsidences or moves, it will lead to the loss of intervertebral height and foraminal stenosis again, resulting in lower limb symptoms [ 28 , 35 , 36 ]. Displacement, loosening and fracture of the internal fixation will also lead to the weakening of the stabilization effect, causing foraminal stenosis and low back pain.…”
Section: Discussionmentioning
confidence: 99%